HUBUNGAN KELENTUKAN PERGELANGAN TANGAN DAN DAYA LEDAK OTOT TUNGKAI TERHADAP KEMAMPUAN UNDER THE BASKET SHOOT PADA TIM BOLA BASKET PUTRA SMP NEGERI 6 PEKANBARU - Sryanti Sarah Lumbanbatu; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problems in this research is athletes often failed in doing under the basket shoot while is not satisfied yet. In addition, athlete’s less knowledge about flexibility of the wrist and leg muscle explosive power that work when doing under the basket shoot. This research was conducted to find out whether there is contribution of flexibility of the wrist and leg muscle explosive power toward the ability of under the basket shoot of female basketball team of junior high school 6 Pekanbaru. The sample collections technique is total sampling with the numbered are 10 athletes of male basketball team junior high school 6 Pekanbaru. This research were used flexibility of the wrist test, vertical jump test, and under basket shoot test. The results in this research are there is relation of flexibility of the wrist toward the ability of under the basket shoot, with correlation is Rx1y= 0,72 with high correlation. There is relation of leg muscle explosive power toward the ability of under the basket shoot, with correlation is Rx2y= 0,81 with high correlation. There is relation of flexibility of the wrist and leg muscle explosive power toward the ability of under the basket shoot, with correlation is Rx1x2y = 0,666 with high correlation.Keywords: Flexibility of the Wrist, Leg Muscle Explosive Power, The ability of Underthe Basket Shoot, Basketball